Efflorescence of Alkali-Activated Cements (Geopolymers) and the Impacts on Material Structures: A Critical Analysis - Longhi, Márlon A.; Zhang, Zuhua; Rodríguez, Erich D.; Kirchheim, Ana Paula; Wang, Hao (Frontiers in Materials, 2019)
Even with the rapid development of the alkali-activated cement (AAC) technology in the past few years, it still needs to be better understood some phenomena that may alter the durability of the material. In many industrial uses and laboratory researches was observed the formation of the salts on the surfacealkali-activated type cements, which was identified as efflorescence. This occurs due to the presence of an alkali transported in contact with the humidity and CO2 environment. It may present externally from the formation of salts on the surface and internally with the carbonation of the alkalis in capillary pores. The effects of efflorescence on the material in use, as well as all factors that can influence its formation are not yet fully understood. This paper presents a critical review about this issue from previous reports (which are very limited in fact, compared with the increasing number of papers and reports on AACs published in the recent years) and scientific knowledge of this physicochemical phenomena.To understand the nature of efflorescence, upon which proper methods of minimising of this issue can be based, the following aspects are discussed and re-examined: (1) the development of efflorescences in PC concrete, (2) the role of alkalis in AACs (3) efflorescence in AACs and (4) effect from physical and microstructural point of view of efflorescences on the ACCs. This paper highlights that the nature of the pore structure and the design parameters (such as alkali concentration, presence of soluble silicates and water content in the activator) are the two most important factors that control efflorescence rate and changes in mechanical behaviour.